1990
DOI: 10.1177/004051759006001107
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Components of Mixed Catalysts

Abstract: The chemical characteristics of mixed catalysts of some organic acids and aluminum sulfate have been investigated. The development of acidity is caused by the complex formation between an organic acid molecule and an aluminum ion, which has been proved by infrared spectra, proton nuclear magnetic resonance spectra, and thin-layer chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…These results support the reaction between the functional groups of serine and the aluminum ion to form a complex to buffer the crosslinking reaction to decrease the reaction kinetics and raise the energies needed to crosslink. Our previous studies2, 19 revealed the formation of a complex between the organic molecules that contain the carboxylic acid and/or other functional groups and the aluminum ion to buffer the crosslinking reaction.…”
Section: Resultsmentioning
confidence: 99%
“…These results support the reaction between the functional groups of serine and the aluminum ion to form a complex to buffer the crosslinking reaction to decrease the reaction kinetics and raise the energies needed to crosslink. Our previous studies2, 19 revealed the formation of a complex between the organic molecules that contain the carboxylic acid and/or other functional groups and the aluminum ion to buffer the crosslinking reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study [7] revealed the complex formed from the interaction between aluminum ion and carboxyl group of tartaric acid in the solution of the mixed aluminum sulfate.…”
Section: Interaction Between the Componentsmentioning
confidence: 99%
“…These results adumbrated that the specific reaction rate constant was affected by the presence of carboxylic acid and amino groups in alpha-amino acid molecules for the kinetic runs. Our previous studies [3,7] pointed out that the carboxylic acid of tartaric acid could interact with aluminum ion to release hydrogen ions to improve the catalytic effect of the crosslinking reaction. The lower values of specific reaction rate constant for the DMDHEU/ alpha-amino acids were suggested by the reason that the interaction between alpha-amino acids and aluminum ion catalyst would decrease the catalytic activity of aluminum ion.…”
Section: Reaction Kineticsmentioning
confidence: 99%
See 2 more Smart Citations